Heutagogy and cybergogy strategies in Indonesian language learning at higher education institutions - Muhammad Sabbardi; Subyantoro; Rahayu Pristi (Universitas Aki, 2024)
This research investigates how the combination of heutagogy and cybergogy can enhance students' abilities in understanding, speaking, reading, and writing in the Indonesian language. Through the General Basic Course (MKDU), the Indonesian language plays a crucial role in education in Indonesia as it is the official language in all fields. The Indonesian language course aims to improve students' communication skills in Indonesian effectively and correctly. In addressing these issues, the discussion context focuses on alternative ideas for teaching approaches in higher education to encourage Indonesian language educators to present learning in an effective and enjoyable manner. To achieve this, the author proposes two strategies: heutagogy, which involves educating by encouraging students to have self-directing skills, and cybergogy, a strategy that incorporates learning by utilizing information technology. The implications of this research can be used as a foundation for the development of language learning methods in higher education institutions.